Problematika dan Analisis Kecurangan untuk Menurunkan Similarity yang Tidak Terdeteksi oleh similarity tool - Prihastini Oktasari Putri; Sri Adi Widodo; Ika Septi Hidayati (Universitas Sarjanawiyata Tamansiswa, 2023)
This research aims to describe the problem of cheating in reducing similarity using Turnitin software in writing scientific articles, as well as the factors causing cheating problems carried out by students. The research method used is qualitative with a case study approach. Data collection techniques include observation, documentation, and interviews with students taking the scientific paper course. The sample consists of students taking the scientific paper course with focus on research mathematics in Open University, Study Program X, using purposive sampling technique. The research findings indicate, there are cheating techniques used to reduce similarity that are undetectable by Turnitin: (1) adjusting spaces in a text that is too large or too small, (2) converting text files into images, (3) adding specific letters to the manuscript, (4) inserting specific small-sized numbers that are almost invisible, (5) intentionally making typing errors, and (6) adding specific symbols to the scientific article manuscript.